2010
DOI: 10.1590/s0104-77602010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Environmental strategy as social practice in a forest-based enterprise: a descriptive study

Abstract: This article aims to study the environmental strategies of a forest-based, cellulose pulp-producing organization by employing strategic theory as social practice and interpretative, descriptive research methods. The analyses of the results show that the studied organization has sought to develop environmental strategies characterized by eco-efficient practices, the mitigation of harmful socio-environmental impacts and the creation of a responsible socio-environmental work ethic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Batista et al [3] produced three-layer particleboard of Pinus elliottii and adding bark of Eucalyptus pellita in the inner layer in three different compositions. Authors concluded that the best results were obtained for panels with minor addition of bark.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Batista et al [3] produced three-layer particleboard of Pinus elliottii and adding bark of Eucalyptus pellita in the inner layer in three different compositions. Authors concluded that the best results were obtained for panels with minor addition of bark.…”
Section: Introductionmentioning
confidence: 99%
“…Particles, in external layers, and Eucalyptus urograndis e Eucalyptus saligna bark in inner layer. Species were chosen because are widely available in Brazil [3].…”
Section: Introductionmentioning
confidence: 99%